Simplify (xy + yz) 2 - 2x2yz. Find the value when x=-1, y = 1 and 2 = 2.7
Answers
Answered by
0
Answer:
(xy+yz)
2
−2x
2
y
2
z when x=−1,y=1,z=2
⇒[y(x+z)]
2
−2x
2
y
2
z
⇒y
2
[x
2
+z
2
+2xz−2x
2
z]
⇒(1)
2
[(−1)
2
+2
2
+2(−1)(2)−2(−1)
2
(2)]
⇒[1+4−4−4]⇒−3
∴(xy+yz)
2
−2x
2
y
2
z at x=−1,y=1 and z=2 is −3
Step-by-step explanation:
Please mark me as brainlist
Answered by
0
Answer:
Step-by-step explanation:
Similar questions
Math,
1 month ago
Accountancy,
1 month ago
Social Sciences,
3 months ago
Social Sciences,
11 months ago
English,
11 months ago
Chemistry,
11 months ago